2017
DOI: 10.1302/0301-620x.99b1.bjj-2016-0398.r1
|View full text |Cite|
|
Sign up to set email alerts
|

Dislocation following total hip arthroplasty using dual mobility acetabular components

Abstract: Based on the current data, the use of DM acetabular components are effective in minimising the risk of instability after both primary and revision THA. This benefit must be balanced against continuing concerns about the additional modularity, and the new mode of failure of intraprosthetic dislocation. Longer term studies are needed to assess the function of these newer materials compared with previous generations. Cite this article: Bone Joint J 2017;99-B(1 Supple A):18-24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 108 publications
6
99
0
8
Order By: Relevance
“…Dual-mobility cups are thought to lower the risk of dislocation by minimizing prosthetic neck impingement and increasing range of motion via the large articulation between the insert and metallic shell [6,25]. The utility of this design concept is borne out by low dislocation rates reported in several studies this decade with cementless dual-mobility cups [6][7][8][9][10][11]. In the current study, there were no dislocations in any subjects.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Dual-mobility cups are thought to lower the risk of dislocation by minimizing prosthetic neck impingement and increasing range of motion via the large articulation between the insert and metallic shell [6,25]. The utility of this design concept is borne out by low dislocation rates reported in several studies this decade with cementless dual-mobility cups [6][7][8][9][10][11]. In the current study, there were no dislocations in any subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Early dual-mobility cups proved adept at decreasing dislocation rates, particularly among elderly patients at high risk for this outcome [5]. Similarly encouraging results have been reported with later-generation dual-mobility cups [6][7][8][9][10][11]. The continued positive safety and performance observed with these designs has extended their use into younger, more active patients [12], as well as the obese [13].…”
Section: Introductionmentioning
confidence: 84%
“…Gwam et al conducted an epidemiological survey using the National Inpatient Samples (NIS) database and found that dislocation‐related acetabular revision occurs in 24.7% of the cases out of 53,508 cases requiring revision surgery. One of the strategies employed to reduce the risk of dislocation in high‐risk patients is to incorporate a dual‐mobility articulation . As the number of THAs has risen each year, the risk of dislocation has remained more or less constant.…”
Section: Introductionmentioning
confidence: 99%
“…однако в условиях реэндопротезирования возможность соблюдения данной рекомендации ограничена вследствие сохранения хорошо фиксированных ножек. не случайно по данным сис тематического обзора I. de Martino с соавторами, средняя частота возникновения внутрипротезных вывихов после ревизий превышает таковую после первичных операций и составляет 1,3% (Sd 2,2%) [32].…”
Section: Introductionunclassified
“…асептическое расшатывание вертлужного компонента двойной мобильности в представленный срок наблюдения развилось в 1 случае в результате травмы. отсутствие механической связанности системы исключает значимую нагрузку на границе «вертлужный компонент -кость» в случае возникновения импинджмента, однако в условиях ревизионного эндопротезирования с дефектами вертлужной впадины отсутствие отверстий для винтов в полусфере немодульных компонентов может ограничить возможность достижения надежной первичной фиксации, если система имплантируется не в антипротрузионный кейдж или бесцементный компонент большого диаметра [32].…”
Section: Introductionunclassified